Factors affecting men's movement through the HIV cascade in the public health services in Cape Town: Perspectives and experiences of health care providers - Madzima, Rutendo (Department of Public Health and Family Medicine, 2017)
The Human Immunodeficiency (HIV) epidemic in South Africa is disproportionately distributed by gender. Although women lead in the number of infections they are at an advantage when it comes to seeking and receiving care. Men's poor health seeking behaviour finds them seeking care late, testing at lower rates, defaulting from treatment and eventually having worse health outcomes. More men than women fail to enter and stay in the HIV cascade of care. The HIV cascade is a metaphor used to describe the steps that include HIV testing, initiation of antiretroviral therapy (ART), adherence, viral suppression and good health outcomes. As health care providers (HCPs) are the ones who interact directly with men in the health system their view of the factors that hinder men's movement through the HIV cascade are valuable to better understanding how men interact with the care system. In this research semi-structured interviews were held with eleven HCPs working with HIV positive patients (6 women, 5 men) across 2 health facilities and 1 non-governmental organisation (NGO) within the Klipfontein sub-district. Health care workers were found to share some of the more commonly held notions regarding the barriers men face in HIV care. However, their experiences offer some challenging ideas and the health systems appears to be realising the need to tailor HIV services to the needs of men. The experiences and perspectives of HCPs should be further explored and the findings used to influence health policies and clinical practice.